Hematopoietic Stem Cell Transplantation and High Dose Chemotherapy in Recurrent and/or Chemotherapy Resistant Hodgkin Lymphoma Cases: A Single Center Experience - Yöntem Yaman; Murat Elli; Kürşat Özdilli; Leyla Telhan; Nihan Bayram; Volkan Hazar; Ebru Tuğrul Sarıbeyoğlu; Şifa Şahin; Seniye Sema Anak (Çocuk Dergisi)
Background: Nearly 20% of patients with Hodgkin Lymphoma (HL) who receive standard treatment will relapse or have a refractory disease. Standard treatment for the Relapsed/Refractory (RR) HL is salvage high dose chemotherapy followed by autologous stem cell transplantation (AuSCT). Management of RR HL after AuSCT with allogeneic stem cell transplantation (ASCT) is also considered as an important salvage therapy.Objective: To describe the outcome in pediatric patients with RR HL who underwent AuHSCT and ASCT in Medipol University hematopoietic stem cell transplantation center.Method: We retrospectively evaluated 18 pediatric patients with RR HL who underwent AHSCT between November 2014 and July 2019. The evaluation of ASCT after RR HL AuSCT is also done.Results: Sixteen patients are still alive. Eleven of them relapsed after AuHSCT. AllogeneicHSCT was performed on 10 patients who relapsed. Relapse was seen in three patients after AHSCT. Eight of them are still alive.